2018
DOI: 10.2147/dddt.s177316
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced oral bioavailability of fluvastatin by using nanosuspensions containing cyclodextrin

Abstract: BackgroundIn this study, fluvastatin (FVT) nanosuspensions containing cyclodextrin were developed to improve oral bioavailability.MethodsFVT nanosuspensions containing cyclodextrin were prepared by a high pressure homogenization technique. The nanosuspensions system was then characterized by transmission electron microscopy (TEM), particle size, differential scanning calorimetry (DSC) and powder X-ray diffractometry (PXRD). In addition, in vitro drug release properties, pharmacokinetics and pharmacodynamics we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Figure 6B which may be due to the dispersion of drug in molecular form in the adhesive and can also be attributed to the small amount of drug present in the formulation. Such behaviour is reported by Li J et al, 2018 in case of fluvastatin -β cyclodextrin nanosuspensions [19], Sharma P et al, 2017 for drug in matrix type of transdermal patch [20 ]. Figure 7A shows characteristic intense peaks between 2θ of 6 and 25, however in case of DIA patch the intensity of peaks were decreased indicating amorphous nature of drug [19] as seen in Figure 7B.…”
Section: Differential Scanning Calorimetrysupporting
confidence: 67%
“…Figure 6B which may be due to the dispersion of drug in molecular form in the adhesive and can also be attributed to the small amount of drug present in the formulation. Such behaviour is reported by Li J et al, 2018 in case of fluvastatin -β cyclodextrin nanosuspensions [19], Sharma P et al, 2017 for drug in matrix type of transdermal patch [20 ]. Figure 7A shows characteristic intense peaks between 2θ of 6 and 25, however in case of DIA patch the intensity of peaks were decreased indicating amorphous nature of drug [19] as seen in Figure 7B.…”
Section: Differential Scanning Calorimetrysupporting
confidence: 67%
“…Pharmacokinetic study demonstrated significant improvement in the oral bioavailability in rabbits by naringenin nanosuspension in comparison to naringenin solution [70]. Pharmacokinetic evaluation of fluvastatin nanosuspensions in rats showed 2.4 folds improvement in bioavailability in comparison to fluvastatin capsule control group [48]. Faster absorption from naproxen nanosuspension decreased time to reach maximum concentration (T max ) by nearly 50% and increased AUC to about 5 folds, when compared to conventional tablet and suspension [55].…”
Section: Nanosuspensions In Drug Delivery Systems Oral Drug Deliverymentioning
confidence: 97%